Coping mechanisms against stigma for people living with HIV/AIDS in Balaka - Nyson, Chikondi (Kamuzu University of Health Sciences, 2022)
The study aimed to explore the coping mechanisms of PLWH against stigma in Balaka. Roy adaptation Model was adopted to guide the researcher in the research process. A qualitative research design was used with a sample size of 10 people both men and women to explore the coping mechanisms. The researcher used random sampling in the selection of the participants. A semi-structured interview guide was used for the purpose of data collection and the data was analysed through content analysis where three themes from the results were identified. These include; knowledge on positive living, forms of stigma and coping strategies e.g. rationalization, seeing oneself as ok, concentrating on other things, acceptance, turning to God, joining a group, disclosing, educating others, changing one's lifestyles and going for counselling. The identified coping strategies have been labelled action based strategies or emotion based coping strategies. Coping appears to be self taught in managing stigma.